STRATEGI PEMBELAJARAN PERCEPATAN TAHFIDZUL QURAN DI PONDOK PESANTREN RAUDLATUL ARIFIN BEJI PASURUAN - Fatimah, Siti; Amaliya Nasucha, Juli (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
This study aims to improve the learning strategy applied in the boarding school by feeling comfortable in memorising the Qur'an according to the target set, research at Raaudlatul Arifin Beji Pasuruan Islamic Boarding School. Qualitative methods will be used in this study, the type of research used is descriptive qualitative, which aims to describe and analyse events, activities and events. The results showed that the learning strategy applied at the Raudlatul Arifin Islamic boarding school is to foster a sense of comfort for each student. With a sense of comfort, it is expected that students can memorise the Koran with focus. Because in memorising the Koran if comfort and peace of mind are disturbed then memorising the Koran cannot be memorised properly. Supporting factors when memorising the Koran include students, teachers, environment, intelligence, motivation. There are also inhibiting factors in memorising the Koran, which include laziness, the age factor of students, family, memorising followed by reading friends